Eocene-Oligocene paleoenvironmental changes in the South Orkney Microcontinent (Antarctica) linked to the opening of Powell Basin - López-Quirós, Adrián; Escutia, Carlota; Etourneau, Johan; Rodríguez-Tovar, Francisco; Roignant, Sabine; Lobo, Francisco; Thompson, Nick; Bijl, Peter; Bohoyo, Fernando; Salzmann, Ulrich; Evangelinos, Dimitris; Salabarnada, Ariadna; et al. (Global and Planetary Change, 2021)
International audience